The Influence of Commitment of Local Head, Government Internal Auditor, Completion of Audit Findings toward Audit Quality and the Implication toward Financial Accountability - Debbie Christine (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The government has been reformed financial management regulation. The study analyzed the effect of the head region commitment, the role of local financial statement quality, and its implication on the local financial performance accountability. The analysis used descriptive and explanatory methods. Analysis carries out at eight local governments in West Java. The data have been collected by using survey technique and distributing questionnaires to the local internal auditor and local external auditor – representative office of West Java. Path analysis applied for hypotheses testing. Finding research, the role of local external auditor has the most significant coefficient influence on the audit's findings. Audit internal function local government has a low contribution to audit quality. Accounting, auditing, and local financial management knowledge would have been improved to produce audit quality. Integrity and timeliness would improve financial performance accountability.